The modified Senning operation - surgical aspects - Krishna Subramony Iyer (Wolters Kluwer Medknow Publications, 2021)
The advent of the arterial switch operation for the treatment of transposition of great arteries (TGA) made the atrial switch operation largely redundant and its use in the developed world is now confined to the atrial component of the double-switch operation for congenitally corrected TGA. In resource-limited countries, however, it remains relevant as a treatment option for patients presenting late with transposition and a regressed left ventricle. The operation is intricate with many potential pitfalls, and this "how I do it" article describes the operative steps in detail to enable surgeons to learn this procedure and make it a part of their surgical armamentarium.